PERANCANGAN SISTEM PENGINGAT BERBASIS ANDROID MENGGUNAKAN GOOGLE MAPS DAN GPS - Indra Usmanan; Sumarsono Sumarsono; Dwi Nugraheny (Compiler, 2013)
Human is perfect creation o f God. Hower, the human ability in processing data in not as effective as computer, as long as the data is saved in the computer memory. By utilizing the computer, such as mobile phone based on android, Google Maps, and GPS, user can make application that can remind the agenda. At this case, the data that has been saved before can be used anytime when needed. This final repot is developed a remainder application based on android using Google Maps and GPS. This system use postgreSQL database the implanted in server. It makes the android smartphone that has been installed with the reminder application become a to client. As the result, the system has some feature. From these feature, the usres are expected to use Android smartphone to help remembering the activities agenda, whenever and wherever.